The Influence of Employee Experience on Workforce Retention in Hybrid Work with Digital Leadership as Moderating Variable - Pungki Syaraswati; Lisa Puspitasari; Sayugo Adi Purwanto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In the wake of widespread adoption of hybrid work arrangements, organizations face challenges in retaining talent. This study investigates the influence of employee experience on workforce retention within a hybrid work environment while examining the moderating effect of digital leadership. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from employees working under hybrid arrangements. The findings reveal that employee experience has a positive and statistically significant effect on workforce retention. Digital leadership also demonstrates a direct positive influence on retention outcomes. The interaction analysis confirms that digital leadership strengthens the relationship between employee experience and workforce retention, indicating an amplifying effect. These results suggest that retention in hybrid settings is not solely driven by flexible work policies or technological infrastructure, but by the capacity of leaders to orchestrate digital collaboration, maintain trust, and provide strategic clarity. The study contributes to contemporary human resource management literature by highlighting the integrative role of digital leadership in transforming work experience into sustained employee commitment. Practical implications emphasize the need for organizations to align hybrid work design with leadership capability development.